2020
DOI: 10.3389/fphys.2019.01568
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis of the Heat Stress Response in Monochamus alternatus Hope (Coleoptera: Cerambycidae)

Abstract: Temperature is a critical factor of insect population abundance and distribution. Monochamus alternatus Hope (Coleoptera: Cerambycidae) is a significant concern since it is transmitted vector of the pinewood nematode posing enormous economic and environmental losses. This pest shows tolerance to heat stress, especially extremely high temperatures. Exposing for 6, 12, 24, 48, or 96 h, the 50% median lethal temperatures (Ltem 50) for fourth-instar larvae were 47.5, 45.5, 43.9, 43.4, and 42.3 • C, respectively. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 73 publications
3
43
0
Order By: Relevance
“…The larvae of M. alternatus were obtained from infested host trees ( Pinus massoniana ) in Jiujiang, Jiangxi Province, China and reared individually on an artificial diet at a constant temperature of 25 ± 0.5°C under a relative humidity (RH) of 60 ± 5% as described by our previous experiment (Li et al ., 2020). Once emergence, adults were individually provided with fresh 1- to 2-year-old P. massoniana twigs.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The larvae of M. alternatus were obtained from infested host trees ( Pinus massoniana ) in Jiujiang, Jiangxi Province, China and reared individually on an artificial diet at a constant temperature of 25 ± 0.5°C under a relative humidity (RH) of 60 ± 5% as described by our previous experiment (Li et al ., 2020). Once emergence, adults were individually provided with fresh 1- to 2-year-old P. massoniana twigs.…”
Section: Methodsmentioning
confidence: 99%
“…M. alternatus showed strong heat tolerance in our previous study (Li et al ., 2020). Only appropriately 50% of the M. alternatus population was deadly damaged when exposed to 42.5°C for 96 h and almost all individuals could endure 40°C for 96 h. This property, in M. alternatus , was achieved for a broad array of adaptive strategies against adverse high temperature, c overing ecological, behavioral, and physiological aspects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pinewood nematode, which is vectored by the pine sawyer beetle M. alternatus , is native to North America and is not considered a primary pathogen of native pines but is the cause of pine wilt in some non-native species [ 41 ]. Using global transcriptome information from previous studies that analyzed the response of M. alternatus to heat stress and pesticides [ 27 , 42 ], a recent comparative study expanded these findings by probing immune-related gene transcript changes in M. alternatus infected by B. xylophilus parasites [ 43 ]. Using high-throughput Illumina RNA-Seq, it was thoroughly demonstrated that the presence of B. xylophilus in M. alternatus adults alters the expression profile of a large number of genes with known or putative immune function.…”
Section: Insect Transcriptomic Response To Infection By Parasitic mentioning
confidence: 99%